(untitled) (Research, Society and Development, 2021)
Objective: To analyze the improvement of the definition of the underlying cause of neonatal deaths before and after death surveillance in Recife, Pernambuco. Methods: A descriptive study that used data from medical certificates of death, confidential data sheets, summaries of investigations. The profiles and the relocation of the underlying cause of death were compared before and after the investigation through specific chapters and groups of the Tenth Revision of the International Classification of Diseases. The agreement was analyzed using the Kappa index. Results: Of the total 144 deaths investigated, 95 (66.0%) had their underlying cause redefined. During the general analysis of the neonatal component, a reasonable agreement index was identified (0.311; CI95%: 0.272-0.350). All ill-defined causes were clarified after surveillance. There was an increment of the preventability potential for all neonatal deaths, with an emphasis on early deaths, which reached 100% causes registered as preventable. Conclusion: Death surveillance made it possible to improve the specificity of the underlying causes described in the medical certificate of death and may contribute to the reorientation of the strategies to reduce neonatal mortality from the perspective of preventability.